Sistem Pakar Diagnosa Kerusakan Pada Gitar Menggunakan Metode Forward Chaining dan Certainty Factor - Billy Gracia; Djoni Haryadi Setiabudi; Justinus Andjarwirawan (Jurnal Infra, 2021)
The guitar is a musical instrument that is in demand by many parties, from beginner to professional musicians. But any musical instrument including the guitar will not be free from damage. There are still many musicians who are confused about the damage they have suffered and do not know what to do with the symptoms they are experiencing. Similar research has been made, namely the application for diagnosing damage to guitars, some using the forward chaining method, some using backward chaining, or dempster-shafers, but in similar studies there is no percentage or level of confidence that can convince users of the diagnostic results, and the user cannot choose how sure to experience the symptoms that occur. Therefore, an expert system is needed to diagnose guitar damage by selecting the symptoms experienced according to the level of confidence, which can detect the damage that occurs and the percentage level of system confidence in the results of the diagnosis to convince the user of the results of the diagnosis..The expert system in diagnosing guitar damage is equipped with Forward Chaining and Certainty Factor methods. The usefulness of Forward Chaining in this diagnostic system is to collect facts or symptoms towards a conclusion, so that users do not need to answer all the questions. By selecting the existing symptoms, a conclusion will be drawn, namely damage. And the use of Certainty Factor in this system is to display the level of system confidence in the results of the diagnosis in the form of a percentage. So that it can convince the user of the diagnostic results.The results of the tests carried out, of the 20 trials by experts, 18 of them have conformity with the results of expert opinion. There are 2 unsuitable trials because the percentage of CF between the probability of damage 1 and 2 is the same, so there is a special case where if the CF percentage of the probability of damage 1 and 2 are the same, then the user can see the solution to the second damage in the Damage Encyclopedia. From the tests carried out, the Expert System with the Forward Chaining and Certainty Factor methods can detect damage to the guitar with an accuracy level of matching the results of the system with expert opinion of 90%.